PENGARUH VARIASI BAFFLE SEGMENTAL PADA HEAT EXCHANGER TERHADAP PRESSURE DROP DAN OVERALL HEAT TRANSFER COEFFICIENT MENGGUNAKAN COMPUTATIONAL FLUID DYNAMICS - Adam Alfakhri (2021)
Heat exchanger on hydraulic power pack unit is used to cool radiator coolant by using hydraulic oil. In carrying out its function, heat exchanger has to allow fluid pressure dropping which shorten the pump's lifetime because it has to work harder. Therefore, in designing heat exchanger, various factors must be considered to achieve optimal results those are having low pressure drop and high overall heat transfer coefficient. One of the factors that must be considered is baffle type used, thus a research is needed to choose optimal baffle type. This research is done by varying baffle type of single segmental, double segmental, and triple segmental with baffle amount 9 and baffle cut 25%. The method used in this research is by using computational fluid dynamics application. Pressure drop gotten by simulation calculation are 6,8887; 3,892; and 3,5607 Pa for baffle types of single segmental, double segmental, and triple segmental, respectively. Overall heat transfer coefficient gotten by simulation calculation are 0,7055; 0,7041; and 0,7005 W/m2.K for baffle types of single segmental, double segmental, and triple segmental, respectively. Double segmental baffle is the optimal segmental baffle type as it could increase the efficiency of the system by 43,5% by only reducing the effectiveness by 0,2%.